Revisiting thiol-yne chemistry: Selective and efficient monoaddition for block and graft copolymer formation - Sprafke, Johannes K.; Spruell, Jason M.; Mattson, Kaila M.; Montarnal, Damien; Mcgrath, Alaina J.; Poetzsch, Robert; Miyajima, Daigo; Hu, Jerry; Latimer, Allegra A.; Voit, Brigitte; Aida, Takuzo; Hawker, Craig J. (Journal of Polymer Science Part A-Polymer Chemistry, 2015)
The untapped potential of radical thiol-yne mono-addition chemistry is exploited to overcome the known limitations of thiol-ene chemistry in polymer coupling and block copolymer formation. By careful choice of alkyne, the reaction can selectively lead to the mono-addition product with efficiencies surpassing those achieved by traditional thiol-ene chemistry. This improvement is illustrated by the nearly quantitative synthesis of a variety of diblock and graft copolymers.
CRIS-Team Scopus Importer:2023-03-20
Keywords: block copolymers; click chemistry; functionalization of polymers; synthesis; thiol-yne